Role of imaging studies in Kawasaki disease - Tsuda, Etsuko; Singhal, Manphool (International journal of rheumatic diseases, 2018)
Kawasaki disease is a medium vessel vasculitis which may be associated with coronary artery abnormalities. Recognition of these abnormalities depends upon various imaging modalities. While two‐dimensional echocardiography remains the first line modality to identify coronary artery abnormalities, it is subject to several fallacies and is operator dependent. Computed tomography coronary angiography is rapidly emerging as a useful imaging modality for better characterization of dilatations, ectasia and aneurysms in the mid‐ and distal segments of coronary arteries. It provides precise details in terms of aneurysm size and morphology. In this review we here described the importance of computed tomography coronary angiography and have also given a brief description of magnetic resonance coronary angiography.